2017
DOI: 10.1063/1.4996294
|View full text |Cite
|
Sign up to set email alerts
|

Unified Hall-Petch description of nano-grain nickel hardness, flow stress and strain rate sensitivity measurements

Abstract: It is shown that: (i) nano-grain nickel flow stress and hardness data at ambient temperature follow a Hall-Petch (H-P) relation over a wide range of grain size; and (ii) accompanying flow stress and strain rate sensitivity measurements follow an analogous H-P relationship for the reciprocal “activation volume”, (1/v*) = (1/A*b) where A* is activation area. Higher temperature flow stress measurements show a greater than expected reduction both in the H-P kε and in v*. The results are connected with smaller nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
4
11
0
Order By: Relevance
“…where f is the fraction of HAGBs, M is the Taylor factor, α, k and σ 0 are material constants, G is the shear modulus, θ LAGB is the average misorientation angle of the LAGBs and b is the Burgers vector. It was shown that the values calculated using this approach are in good agreement with experimental results [11,30,43,[46][47][48]. Furthermore, the applicability of this model is also confirmed in the present work because the datum points corresponding to samples processed only by HPT with a small numbers of turns tend to lie below the trend line in Fig.…”
Section: The Significance Of Gb Characteristics On the Hall-petch Relsupporting
confidence: 88%
“…where f is the fraction of HAGBs, M is the Taylor factor, α, k and σ 0 are material constants, G is the shear modulus, θ LAGB is the average misorientation angle of the LAGBs and b is the Burgers vector. It was shown that the values calculated using this approach are in good agreement with experimental results [11,30,43,[46][47][48]. Furthermore, the applicability of this model is also confirmed in the present work because the datum points corresponding to samples processed only by HPT with a small numbers of turns tend to lie below the trend line in Fig.…”
Section: The Significance Of Gb Characteristics On the Hall-petch Relsupporting
confidence: 88%
“…Calculated values of v* from Equation (6) showed an agreement with the additional increase in order of magnitude measurements [50]. These higher nano-scale dimensions seem reasonable with respect to individual atomic displacements being associated with grain boundary shearing deformations.…”
Section: Nanograin Size Weakeningsupporting
confidence: 72%
“…Whereas, the (1/v*) values are shown to increase by an order of magnitude between conventional and nano-scale grain sizes, there is an additional order-of-magnitude increase to atomic-scale dimensions for the grain size weakening behavior that itself is strain rate dependent, as demonstrated in Figure 4 for connection of the lower (1/v*) value for the 40 nm grain size material tested at (dε/dt) = 1.04 s −1 as compared with the higher value at a creep-connected strain rate 10 −5 times slower [49]. Calculated values of v* from Equation (6) showed an agreement with the additional increase in order of magnitude measurements [50]. These higher nano-scale dimensions seem reasonable with respect to individual atomic displacements being associated with grain boundary shearing deformations.…”
Section: Nanograin Size Weakeningsupporting
confidence: 65%
See 1 more Smart Citation
“…Material strengthening due to grain size refinement may be expressed by the Hall-Petch relationship: where σ ε is the true stress at true strain ε, σ 0ε is friction stress, k ε is microstructural stress intensity, and d is average grain diameter. The value of ε may be the initial yield strain or proof strain that is determined for yielding or the subsequent strain for a plastic flow stress that is finally terminated in fracturing [ 30 ]. In the dislocation pile-up model, k ε is related to the concentration stress, τ C , as k ε = m T (π m S G b τ C /2 α) 1/2 In Equation (3), m T and m S are Taylor and Sachs orientation factors, G shear modulus, b magnitude of the Burgers vector, and α, a numerical factor following from the mutual dislocation interactions.…”
Section: Discussionmentioning
confidence: 99%